Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/678387
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Climbing Ability and Physiological Responses to Rock Climbing

Abstract: Aim. The aim of this study was to examine the relationship between submaximal and maximal physiological responses to rock climbing for climbers of differing abilities. Methods. Twenty-six male climbers performed a submaximal climbing test on a known circuit at 90° (vertical) and 105° (15° overhanging) inclination and speed 25 movements·min−1. A maximal test was undertaken on a similar circuit at the same speed with inclination increasing by 10° for each successive 3 min stage. Results. Mean oxygen consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…Modern rock climbing, which is often performed on steep faces, is also likely to require a notable anaerobic contribution from the forearm flexors, particularly during the latter stages before exhaustion occurs (31), or during powerful moves used during the crux (most difficult) sections of a route. Furthermore, rock climbing performance encompasses psychological aspects such as perception affordance (7), and technical components such as footwork efficiency (4), handgrip strength (3), climber flexibility (8), and improved exercise economy (5). Although the current study provides important data to highlight the importance of a sport specific aerobic capacity and forearm oxidative capacity index, it should be noted that this study assessed the oxidative capacity index and maximal de-oxygenation which provides a complete representation of the capacity of the forearm to deliver and utilize oxygen within one flexor.…”
Section: Discussionmentioning
confidence: 99%
“…Modern rock climbing, which is often performed on steep faces, is also likely to require a notable anaerobic contribution from the forearm flexors, particularly during the latter stages before exhaustion occurs (31), or during powerful moves used during the crux (most difficult) sections of a route. Furthermore, rock climbing performance encompasses psychological aspects such as perception affordance (7), and technical components such as footwork efficiency (4), handgrip strength (3), climber flexibility (8), and improved exercise economy (5). Although the current study provides important data to highlight the importance of a sport specific aerobic capacity and forearm oxidative capacity index, it should be noted that this study assessed the oxidative capacity index and maximal de-oxygenation which provides a complete representation of the capacity of the forearm to deliver and utilize oxygen within one flexor.…”
Section: Discussionmentioning
confidence: 99%
“…Rock climbing is an increasingly popular recreational and competitive sport, with a growing research base (Watts, 2004;España Romero, 2009;Draper et al, 2011a;Baláš et al, 2014). As the sport has developed the number of disciplines has increased and now includes such diverse activities as mountaineering, big wall climbing, bouldering, deep water soloing, sport climbing, traditional climbing, ice climbing and mixed climbing (MacLeod et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An important parameter in _ VO 2 consumption seems to be climbing experience or climbing technique, as reported by both Draper, Jones, Fryer, Hodgson, and Blackwell (2008) and Baláš et al (2014). Both authors demonstrated that climbers with higher climbing experience, expressed as years of climbing or climbing ability, had substantially lower oxygen cost during submaximal climbing than lower grade climbers.…”
Section: Discussionmentioning
confidence: 75%
“…They proposed that total ascent time should be around 150 min per week to match the American College of Sport Medicine recommendations for activity levels (Garber et al, 2011); this is the equivalent to approximately 500 -750 metres of climbing, per week (Rodio et al, 2008). Several other studies have documented _ VO 2 consumption during various climbing protocols at between 20 and 45 ml·kg 21 ·min 21 ; they have also demonstrated that total _ VO 2 consumption is influenced by other factors, such as locomotion pace, climbing difficulty, steepness of the wall, climbing style and climbing ability (Baláš et al, 2014;de Geus, O'Driscoll, & Meeusen, 2006;Draper, Jones, Fryer, Hodgson, & Blackwell, 2010;Mermier, Robergs, McMinn, & Heyward, 1997;Sheel, Seddon, Knight, McKenzie, & Warburton, 2003;Watts, 2004).…”
Section: Introductionmentioning
confidence: 99%